Analisis Faktor-Faktor yang Mendorong Keputusan Pembelian Konsumen ii Ipo Morning Coffee Garut - Dody Hermana; Rahyuniati Setiawan; David Saputra (Fakultas Ekonomi Universitas Garut, 2019)
The purpose of this study was to find out what factors drove consumer purchase decision at Ipo Morning Coffee Garut. The purpose of this research is to find out the factors which gives an impact on purchase decisions consumers at Ipo Morning Coffee Garut. The research methods used in this study are quantitative metode with the multivariate statistical intervendency approach, and data analysis techniques in this study use exploratory factor analysis technique. Data collection techniques used are library studies and field studies such as observation, interview,and questionnaires. The unit of measurement of data used for the manufacture of the questionnaire is the unit of measurement of the scoring data and use a likert scale.The population in this study were consumers at Ipo Morning Coffee Garut. The sample collection used in this study was probability sampling technique, namely the insidental sample of 96 respondents. The results of this study there are 13 variables studied and the process of the 13 variables are valid all and formed into new factors. After the extraction and rotation process, which has a correlation value there are only four components that are formed correctly, including factors in personality, price factors, lifestyle factors, and involvement factors.